The Trajectories of Separation: Transatlantic Networks, Disciplinary Boundaries, and the Isolated Histories of Mizrahim - Gerber, Noah S.; Moreno, Aviad (AJS Review: The Journal of the Association for Jewish Studies, 2025)
Most sociological and ethnographical studies of Israeli Mizrahim are disconnected from those of Sephardic and MENA Jewish communities worldwide. Rooted in academic cultures that predate the country's establishment, Mizrahi history in Israel is often deemed either a success story or a shameful story of marginalization in these communities' global histories, and as a sui generis case of Jewish migration. We trace the early origins of this seemingly arbitrary disconnect to nineteenth-century European scholarship on "Sephardic" turned "Oriental" Jews and follow its subsequent entrenchment not only in Mandate Palestine and Israel but also in the United States. By focusing on key scholars working across transregional networks, we show how a Sephardic bias evolved into disciplinary divisions that have constrained the development of MENA Jewish studies. Finally, we call for renewed attention to the historical and contemporary patterns of separation, diffusion, and diasporic mobility that have long characterized MENA Jewish communities.
Keywords: Judaïsme – Djerba; Judaïsme – Mzab

Rapatriement en France métropolitaine et migration en Israël des Juifs d’Algérie : deux faces d’une expérience migratoire postcoloniale - Scioldo-Zürcher, Yann (Archives Juives, 2025)
Keywords: Judaïsme – Mzab